Risk and associated factors of depression and anxiety in men with prostate cancer: Results from a German multicenter study. Issue 10 (29th July 2020) - Esser, Peter; Mehnert‐Theuerkauf, Anja; Friedrich, Michael; Johansen, Christoffer; Brähler, Elmar; Faller, Hermann; Härter, Martin; Koch, Uwe; Schulz, Holger; Wegscheider, Karl; Weis, Joachim; Kuba, Katharina; et al.
Abstract: Objective: In order to optimize psycho‐oncological care, studies that quantify the extent of distress and identify certain risk groups are needed. Among patients with prostate cancer (PCa), findings on depression and anxiety are limited. Methods: We analyzed data of PCa patients selected from a German multi‐center study. Depression and anxiety were assessed with the PHQ‐9 and the GAD‐7 (cut‐off ≥7). We provided physical symptom burden, calculated absolute and relative risk ( AR and RR ) of depression and anxiety across patient subsets and between patients and the general population (GP) and tested age as a moderator within the relationship of disease‐specific symptoms with depression and anxiety. Results: Among 636 participants, the majority reported disease‐specific problems (sexuality: 60%; urination: 52%). AR for depression and anxiety was 23% and 22%, respectively. Significant RR were small, with higher risks of distress in patients who are younger (eg, RR depression = 1.15; 95%‐ CI : 1.06‐1.26), treated with chemotherapy ( RR depression = 1.46; 95%‐ CI : 1.09‐1.96) or having metastases ( RR depression = 1.30; 95%‐ CI : 1.02‐1.65). Risk of distress was slightly elevated compared to GP (eg, RR depression = 1.13; 95%‐ CI : 1.07‐1.19). Age moderated the relationship between symptoms and anxiety (Burination = −0.10, P = .02; Bsexuality = −0.11, P = .01). Conclusions: Younger patients, those with metastases or treatment with chemotherapy seem to be at elevated risk for distress and should be closely monitored. Many patients suffer from disease‐specific symptom burden, by which younger patients seem to be particularly distressed. Support of coping mechanisms associated with disease‐specific symptom burden seems warranted.